La disolución de la categoría de identidad: la aproximación deconstructiva del pensamiento de Nancy Fraser (2010)
Nancy Fraser; American philosopher; argues that claims for recognition of difference push at present; many social conflicts in the world and cover a wide range of aspirations; from the emancipation to the more openly roundly rejected. This multiplicity of movements seeking to express their demands through the language of recognition. Today; the claim of identity supplants class interest and makes it the best means of social mobilization. This new vision requires to Guild an intellectual and practical enterprise; which must be the dissolution of the concept of identity as a category of social analysis. The author proposes the model s status as an alternative model in this configuration. What requires recognition is not group-specific identity but the status of individual members of a group as full participants in social interaction. To participate fully in a social group requires a new model of justice that has the capacity to sustain the lack of recognition and cultural value can not be understood apart from economic conditions and can not block the distribution of wealth. Also economic reasons; such as income distribution; counts as subtext for the recognition. Only considering both dimensions simultaneously it is possible to determine what prevents equal participation in a particular case. This is achieved by analyzing the overlap between recognition and redistribution to determine what is the best way to remedy the injustice.